Combination treatment of low-fluence Q-switched Nd:YAG laser and oral tranexamic acid for post-inflammatory hyperpigmentation due to allergic contact dermatitis to henna hair dye. (17th February 2016) - Lee, Young Bok; Park, Sae Mi; Kim, Jin-Wou; Yu, Dong Soo
Abstract : A 64-year-old female presented with facial hyperpigmentation. She had dyed her hair monthly with pure henna powder for the past seven months. After patch tests, the patient was diagnosed as post-inflammatory hyperpigmentastion due to allergic contact dermatitis to pure henna that has rarely been reported. The patient underwent Q-switched Nd:YAG laser treatment and was treated with oral tranexamic acid for 10 weeks. The hyperpigmentation on her forehead demonstrated substantial improvement.